Percutaneous Trigeminal Ganglion Balloon Compression Rhizotomy: Experience in 27 Patients - Tadej Strojnik; Tomaž Ŝmigoc (The Scientific World Journal)
Purpose. Percutaneous ganglion balloon compression (PBC) is a minimally invasive procedure for treatment of trigeminal neuralgia. Materials and Methods. Twenty-seven (19 female and 8 male) patients, who presented with classical symptoms of trigeminal neuralgia, were included. Age ranged from 34 to 91 years (median 62 years), 33 procedures were performed. Duration of the symptoms ranged from 1 year to 30 years (median 5 years). Results. After the procedure, pain relief was reported in 25 (93%) patients. In two patients, the pain remained the same. The pain free period ranged from 2 to 74 months (median 15 months). A mean duration of analgesia was longer in patients with ideal pear shape of balloon at the time of the procedure compared to nonideal shape (P=0.01). No major complications occurred in our group of patients. Conclusions. Percutaneous trigeminal ganglion balloon compression is a safe, simple, and effective method for temporary pain relief in a selective group of trigeminal neuralgia patients.